Landmark cases in criminal law - Handler, Philip; Mares, Henry; Williams, Ian Scott (Hart Publishing, 2017)
Landmark cases and wider themes in criminal law / Philip Handler, Henry Mares, and Ian Williams -- The Carrier's case / Ian Williams -- R.V. Saunders and Archer / John Baker -- R.V. Jones / Simon Stern -- R.V. Bembridge / Jeremy Horder -- R. V. Shipley (1784) : the Dean of St. Asaph? case / Kevin Crosby -- McNaghten's case / Arlie Loughnan -- R.V. Flattery / Rebecca Williams -- DPP v. Beard / Philip Handler -- R.V. Jordan / David Ibbetson -- Shaw v. DPP / Henry Mares -- DPP v. Morgan / Lindsay Farmer -- Whitehouse v. Lemon, Whitehouse v. gay news Ltd / John Pencer -- R.V. Hancock and Shankland / Matthew Dyson -- R.V. Howe / Findlay Stark -- R.V. Brown / Jonathan Herring